IMPACTUL COMUNICĂRII MANAGERIALE ASUPRA ACTIVITĂŢII INSTITUŢIEI PREŞCOLARE - USM ADMIN (Moldova State University, 2011)
In this article there is described the communication process on pre-school institution and the data from an experiment on the level of communication of managers on the teacher's meetings is analyzed. There was also briefly described and analyzed the model of effective communication between manager and subordinates.